(untitled) (National Administration Journal, 2020)
The current environment among the members of a company determines an organizational environment based on emotional states as a result of the workers’ perception of various aspects within their company. Therefore, the organizational environment is reflected in the workers’ behavior and performance. This study shows the relationships found between the dimensions of organizational environment and work performance. The results demonstrate that leadership and interpersonal relationships are significantly correlated with work performance.